PROPORSI MANGGA PODANG-PISANG KEPOK DAN KONSENTRASI JERUK NIPIS TERHADAP KARAKTERISTIK FRUIT LEATHER MANGGA - Rejeki, Fungki Sri; Anggita, Della; Wedowati, Endang Retno (2477 - 6165, 2019)
Fruit leather is a snack made from fruit puree in the form of thin sheets, plastic texture, and does not break when rolled. The raw material used was a podang mango extract. The component of pectin, acid, and sugar affect the fruit leather texture. Addition ofkepok banana puree needed as a source of pectin. Furthermore, the addition of ime juice to reduce pH on mixed puree. Randomized Block Design used with two factors and three replications. The first factor was the proportion of podang mango extract and kepok banana puree (90:10; 80:20; 70:30). The second factor was a concentration of lime juice (0%; 0,4%; 0,8%). The parameters observed were yield, pH, moisture content, crude fiber content, reducing sugar content, aroma, flavor, and texture. The research result showed that the best treatment was 80% podang mango extract, 20% kepok banana puree, and 0.4% lime juice.